The development of rheumatology at the stage of formation of a new technological paradigm - T. V. Beketova (Научно-практическая ревматология)
Using rheumatology as an example, the paper considers current trends in the development of medical science in the 21st century. It is emphasized that biochemistry,  genetics, and molecular biology are becoming the central research priority site attracting to clinical medicine and rheumatology,  neuroscience  (including cognitive and computational neurobiology, neuroinformatics), and psychology. Modern rheumatology effectively adapts current scientific achievements, which contributes to the significant progress of fundamental  and clinical medicine. Deciphering the key immune mechanisms of the pathogenesis of immune-mediated inflammatory rheumatic diseases (IIRD) has allowed biotechnology techniques to be used to design fundamentally new drugs, such as biological agents, small molecules that are able to selectively affect certain pathogenetic constituents  and to minimize the overall functioning of the immune system. This could substantially enhance the efficiency of treatment for IIRDs,  by achieving a long-term  stable remission in many patients and contributed  to a significant expansion of ideas on human pathology. It is assumed that most promising studies of pharmacotherapy for IIRDs towards personalized medicine will be based on postgenomic technologies, including proteomics,  transcriptomics, metabolomics,  epigenomics, as well as the integrated use of digital methods.